The Effectiveness of Group Counseling using Role Reversal Technique in Improving Social skills of Inclusive Students - Ratih Christiana; Dahlia Novarianing Asri (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aimed to examine the effectiveness of group counseling using the role reversal technique in improving students’ social skills. The background of this research was based on students’ low social interaction abilities, including cooperation, empathy, and interpersonal communication. The study employed a quantitative approach with a one-group pretest–posttest design. The research subjects consisted of eight junior high school students with low levels of social skills, who were assigned to an experimental group. The research instrument was a social skills questionnaire covering the following indicators: empathy ability, communication and social interaction, openness, helping behavior, and self-understanding, which had been tested for validity and reliability. Data analysis was conducted using a t-test. The results showed a significant improvement in social skills among students in the experimental group after participating in group counseling with the role reversal technique. In conclusion, group counseling using the role reversal technique is effective in improving students’ social skills.